The Diversity of a Polyclonal FluCell‐SELEX Library Outperforms Individual Aptamers as Emerging Diagnostic Tools for the Identification of Carbapenem Resistant Pseudomonas aeruginosa. Issue 64 (15th October 2020) - Kubiczek, Dennis; Raber, Heinz; Bodenberger, Nicholas; Oswald, Thomas; Sahan, Melis; Mayer, Daniel; Wiese, Sebastian; Stenger, Steffen; Weil, Tanja; Rosenau, Frank
Abstract: Textbook procedures require the use of individual aptamers enriched in SELEX libraries which are subsequently chemically synthesized after their biochemical characterization. Here we show that this reduction of the available sequence space of large libraries and thus the diversity of binding molecules reduces the labelling efficiency and fidelity of selected single aptamers towards different strains of the human pathogen Pseudomonas aeruginosa compared to a polyclonal aptamer library enriched by a whole‐cell‐SELEX involving fluorescent aptamers. The library outperformed single aptamers in reliable and specific targeting of different clinically relevant strains, allowed to inhibit virulence associated cellular functions and identification of bound cell surface targets by aptamer based affinity purification and mass spectrometry. The stunning ease of this FluCell‐SELEX and the convincing performance of the P. aeruginosa specific library may pave the way towards generally new and efficient diagnostic techniques based on polyclonal aptamer libraries not only in clinical microbiology. Abstract : Team or superstar? You should never walk alone : Individual aptamers evolved against bacterial surfaces bind very specific but tend to miss molecular targets. However, the large number of aptamers and the large sequence space of polyclonal libraries ensure identification of pathogens with high fidelity.